2015
DOI: 10.1186/2055-0928-1-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutritional composition on the glycemic index and glycemic load values of selected Emirati foods

Abstract: Background: Population-based studies have shown an association between health, food composition, and diets; therefore, data on the composition of traditional foods for meal planning, nutritional assessment, and clinical nutrition research to build up a relevant database are needed. Methods: The objective of this study was to assess the effect of the nutritional composition of five commonly consumed traditional Emirati foods, Threed chicken, Marqoqa, Gurus, Assidah, and Saqo, on the glycemic index (GI) and glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…This might be correct because, the GIs and GLs of LPY (68.33%; 34.67) and LPYTOS (60.33%; 31.67) were still significantly higher than that of APYTOS (46.00%; 23.33), IPYTOS (48.67%; 25.00) and EPYAH (50.33%; 26.00) despite the significant high protein cum high fat and fiber contents of LPY shown in Table 1. In consistent with this position, Al Dhaheri et al [29] reported that; Gurus with high fiber (4.11 ± 0.73 g), protein (8.76 ± 0.16 g) and fat (7.71 ± 0.90 g) contents still had high GI value of 71.7% due to its cooking method, and findings about LPY tend to be in consonance with their findings. According to Aston et al [30], GI does not just measure the carbohydrate absorption in the small intestine directly, but also indicates the effect of other factors in the foods that can influence the rate of carbohydrate absorption in small intestine, which would in turn influence GI.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This might be correct because, the GIs and GLs of LPY (68.33%; 34.67) and LPYTOS (60.33%; 31.67) were still significantly higher than that of APYTOS (46.00%; 23.33), IPYTOS (48.67%; 25.00) and EPYAH (50.33%; 26.00) despite the significant high protein cum high fat and fiber contents of LPY shown in Table 1. In consistent with this position, Al Dhaheri et al [29] reported that; Gurus with high fiber (4.11 ± 0.73 g), protein (8.76 ± 0.16 g) and fat (7.71 ± 0.90 g) contents still had high GI value of 71.7% due to its cooking method, and findings about LPY tend to be in consonance with their findings. According to Aston et al [30], GI does not just measure the carbohydrate absorption in the small intestine directly, but also indicates the effect of other factors in the foods that can influence the rate of carbohydrate absorption in small intestine, which would in turn influence GI.…”
Section: Discussionsupporting
confidence: 52%
“…Alinnor and Akalezi [33] reported 40.61% of carbohydrate for uncooked white yam and 33.76% when it was cooked and used to make LPY. Similarly, Al Dhaheri et al [29] found that cooking method's effect played role in increasing food's moisture content. Using biochemical reasoning, differences would consequently occur in the rate of release of glucose into the body as well as in blood glucose levels that would likely cause GI to vary and this further establish the potential effects of processing and cooking methods on GI and concurrently GL via proximate composition.…”
Section: Discussionmentioning
confidence: 96%
“…Taking into consideration that participants' characteristics such as age, sex, bodymass index and ethnicity are not supposed to influence GI determination (Wolever et al, 2003). In addition, similar studies have been conducted on female subjects only (Amano et al, 2004: Al Dhaheri et al, 2015. Participants did not take part if they had any of the exclusion criteria, defined as: aged less than 18 or more than 25 years old; if they had their menstrual cycle; body mass index (BMI) value more than or equal to 25 kg/m 2 or less than 18.5 kg/m 2 ; fasting plasma glucose (FPG) value of more than 6.1 mmol/l; and having a known history of impaired glucose tolerance or DM.…”
Section: Subjectsmentioning
confidence: 99%
“…Similarly, this occurs with dietary fiber, protein, and fats, which are nutritional compounds that form heavy molecular complexes that slow down carbohydrates' digestion, and supposedly, reduces the foods' GI [20]. Heterogenous results were found within GFB samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are associated with the early development of non-communicable diseases (NCD) such as diabetes and overweight [17]. Furthermore, in the case of individuals adhering to a GFD, the ingredients commonly used in the formulations have high GIs, and the risk of developing NCD may be higher [18][19][20].…”
Section: Introductionmentioning
confidence: 99%